Suprapubic Bladder Catheterization of Male Spinal-Cord–Injured Sprague–Dawley Rats - Robinson, Mary A (American Association for Laboratory Animal Science, 2012)
The rat spinal-cord–injury (SCI) model is widely used to study the pathologic mechanisms that contribute to sensory and motor dysfunction in humans. This model is thought to mimic many of the negative outcomes experienced by humans after spinal contusion injury. We theorized that manual bladder expression contributed to the kidney and bladder lesions reported in previous studies using the rat SCI model. In the present study, rats were surgically implanted with bladder catheters after spinal contusion injury to provide continuous drainage of urine. After 72 h, the rats were euthanized and their kidneys and bladders examined histologically. BUN, serum creatinine, and urine protein were compared at 0 and 72 h after surgery. Kidney and bladder lesions were similar in SCI rats with and without implanted bladder catheters. BUN at 72 h was higher than baseline values in both groups, whereas serum creatinine was higher at 72 h compared with baseline values only in the catheterized rats. These findings indicate that suprapubic bladder catheterization does not reduce hydronephrosis in SCI rats and that the standard of care for bladder evacuation should continue to be manual expression of urine.